Produção de roteiro escrito e visual (storyboard) de jogo digital sobre patrimônio cultural - Renata Passos Freire Ferreira (2023)
This study highlights the relevance of incorporating digital games into students' daily lives as a means of enriching pedagogical practices, making learning more engaging, collaborative and meaningful. In addition, it focuses on the development of digital game scripts (ARRUDA, 2014; OLIVEIRA, 2017; 2020) focused on students' local heritage, as an effective strategy to establish a deeper connection between the school and students' lives. This approach strengthens local cultural and historical identity and broadens community participation, contributing to social, political and economic transformations. The innovative integration of digital game scripts, cultural heritage, culture and identity within the educational context is explored in this study that investigates a hitherto underutilized genre of discourse in the school curriculum and examines how language, multimodality and technology can influence students' cultural identity and social practices. This qualitative research was conducted to promote appreciation, understanding and transformation of the local environment of students, adopting a decolonial perspective in relation to culture, identity, heritage and language (TOLENTINO, 2012; 2016; 2018). Interviews revealed the lack of knowledge about the origin of the names of the school, pointing out the need for investigation in this aspect. The creation of different types of texts – written, oral and visual – played a key role in documenting the heritage identified by the students, while also evidencing that, despite the challenges faced, students have a positive appreciation of their environment. In addition, this approach promoted the development of several skills, such as critical analysis, research, group work, writing, reading, interpretation of multisemiotic texts, oral presentation and argumentation. The promotion of competencies in the classroom has also resulted in increased protagonism, engagement, creativity and autonomy of students, encouraging deep reflection on their identities and their role in the community. The prospect of future professionalization as screenwriters of digital games also aroused great interest among students. The teacher played a key role as a mediator of learning, facilitating the academic, social and professional progress of students through problem solving. The results of this study highlight the importance of research such as this and indicate the need to deepen the conceptions of cultural heritage, identity and culture in education. In addition, they highlight the importance of stimulating pleasure through writing and visual expression in pedagogical practices.